How cancer patients and oncologist assess data-sharing and the risk of re-identification in genomic research?: ethical implications for informed consent and governance - Winkler, Eva C.; Schleidgen, Sebastian; Schickhardt, Christoph; Kalle, Christof von; Ose, Dominik; Husedzinovic, Alma (Journal of clinical oncology, 2016)
e18186Background: Data-sharing among genomic researchers is promoted for its potential to accelerate our understanding of the molecular basis of cancer. However, with genomic data sharing the risks of re-identifying study participants and revealing personal genomic information rises. This study aims at exploring perceptions of patients and physicians in Oncology regarding their assessment of the informational risks resulting from participating in whole genomic research studies in order to improve the informed consent process. Methods: We conducted a qualitative focus group study at the National Center for Tumor Diseases (NCT) with five focus groups of cancer patients (n = 16) and two focus groups of oncologists (n = 8). Group discussions were structured and took 75 minutes on average. They were transcribed verbatim, coded and analyzed following qualitative content analysis. Results: Patients and oncologists assessed the informational risks either as minimal or greater than minimal, depending on the context factors of occupational status, age and prognosis of genomic research participants. Interestingly, even patients who assumed a greater risk did not refrain from participating in genomic research, provided that certain informational as well as institutional safeguards are implemented. Moreover, they expected comprehensive disclosure of the risks resulting from genomic data sharing. Conclusions: The results suggest 1) comprehensive disclosure of the risks of genomic research to potential study participants in genomic research to facilitate risk assessment and sound decision making, 2) establishing independent governance entities in order to minimize the informational risks of genomic research, and 3) policies which offer guidance for physicians and researchers involved in genomic research. Solutions for 1-3 have been implemented at the NCT and will be presented.
Conference abstract, 2016 ASCO annual meeting
Gesehen am 23.04.2021